Aurora‐A Kinase: A Potent Oncogene and Target for Cancer Therapy. Issue 6 (13th July 2016) - Yan, Min; Wang, Chunli; He, Bin; Yang, Mengying; Tong, Mengying; Long, Zijie; Liu, Bing; Peng, Fei; Xu, Lingzhi; Zhang, Yan; Liang, Dapeng; Lei, Haixin; et al.
Abstract: The Aurora kinase family is comprised of three serine/threonine kinases, Aurora‐A, Aurora‐B, and Aurora‐C. Among these, Aurora‐A and Aurora‐B play central roles in mitosis, whereas Aurora‐C executes unique roles in meiosis. Overexpression or gene amplification of Aurora kinases has been reported in a broad range of human malignancies, pointing to their role as potent oncogenes in tumorigenesis. Aurora kinases therefore represent promising targets for anticancer therapeutics. A number of Aurora kinase inhibitors (AKIs) have been generated; some of which are currently undergoing clinical evaluation. Recent studies have unveiled novel unexpected functions of Aurora kinases during cancer development and the mechanisms underlying the anticancer actions of AKIs. In this review, we discuss the most recent advances in Aurora‐A kinase research and targeted cancer therapy, focusing on the oncogenic roles and signaling pathways of Aurora‐A kinases in promoting tumorigenesis, the recent preclinical and clinical AKI data, and potential alternative routes for Aurora‐A kinase inhibition.